2018
DOI: 10.1186/s12891-018-2051-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three patient reported outcome measures following operative fixation of closed ankle fractures

Abstract: BackgroundSeveral patient reported outcome measures (PROMs) are available for assessing the outcomes of ankle fracture but few have been compared for recommended measurement properties. This study compares the measurement properties of the Lower Extremity Function Scale (LEFS), Olerud Molander Ankle Score (OMAS) and Self-Reported Foot and Ankle Score (SEFAS) following ankle surgery.MethodsThe retrospective cohort study included 959 patients aged 18 years and over who underwent surgical treatment (ORIF) for uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 26 publications
2
69
1
Order By: Relevance
“…The main outcome of OMAS is a well-established outcome score that has been validated for ankle fractures. 9 This study is also to our knowledge the first randomized controlled trial to compare the use of an ankle trainer versus conventional physiotherapy after surgically treated ankle fractures.…”
Section: Discussionmentioning
confidence: 98%
“…The main outcome of OMAS is a well-established outcome score that has been validated for ankle fractures. 9 This study is also to our knowledge the first randomized controlled trial to compare the use of an ankle trainer versus conventional physiotherapy after surgically treated ankle fractures.…”
Section: Discussionmentioning
confidence: 98%
“…This review highlights frequency of use of particular outcome measures over others in clinical trials of non-pharmacological interventions for ankle fracture, most notably the OMAS. Despite some evidence for the validity and reliability of the OMAS [25, 26], there is debate amongst clinicians and researchers regarding its suitability for use, particularly with regard to the lack of a formal development process and a systematic review highlighted concerns with this in particular [11]. The research group recommended the use of a newer PROM, developed in 2014 specifically for this injury, known as the Ankle Fracture Outcome of Rehabilitation Measure (A-FORM) [27].…”
Section: Discussionmentioning
confidence: 99%
“…A final score is calculated from 0 to 100, with 100 representing a better functional outcome. A recent study found that the OMAS had acceptable levels of internal consistency and test-retest validity, and correlated strongly with other lower limb injury outcome scoring systems and measures of general health, including the EQ-5D [29]. The primary null hypothesis is that there is no difference in outcome (primary outcome measure, OMAS) after 1 year between fixation of associated medial malleolus fractures and non-fixation in patients undergoing surgery for an unstable fracture of the ankle.…”
Section: Methodsmentioning
confidence: 99%